Exploring the effect of MBKM as a New Curriculum in Indonesia - Reli Handayani; Ahmad Alra Dani; Saharudin; Tubagus Zam Zam Al Arif (Eduvelop: Journal of English Education and Development, 2024)
Higher education in Indonesia has faced significant challenges in presenting a curriculum that is responsive and relevant to the demands of the times. The Competency-Based Education Model (MBKM) has been adopted as a new approach in updating the college curriculum. This study aims to explore the influence of MBKM as a new curriculum in Indonesia. The research methods used qualitative analysis through interviews, surveys, and literature studies. The findings show that the implementation of MBKM has had a significant impact in strengthening students' skills, knowledge, and attitudes. In addition, MBKM has also changed the learning paradigm from a center of teaching activities to a center of competency achievement. However, challenges remain in integrating MBKM into the established academic culture and improving the quality of implementation consistently across universities in Indonesia. The implication of this research is the need for continuous support from various stakeholders to ensure the sustainability and effectiveness of MBKM as a new curriculum that is competitive in the global context. Further research is also needed to evaluate the long-term impact of MBKM implementation on the quality of higher education in Indonesia, These include requiring courses as prerequisites, improving coordination with schools, modifying curriculum order, and clarifying credit transfer policies.